(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Abundant embryogenic callus was obtained from leaf and floral explants of "Chancellor" grape by continuous culture for 12 weeks on Nitsch and Nitsch basal medium supplemented with 9 μM 2, 4-D + 17 μM IASP + either 1 μM BA or 1 μM TDZ (ECIM) in darkness. They were successfully maintained by a five to six week subculture interval on NN medium containing 2 μM 2, 4-D + 0.2 μM TDZ + 4 μM IASP (LTMM). Near synchronous embryo developed from embryogenic callus on medium containing 10 μM IASP + 8 μM NOA + 1 μM TDZ + 1 μM ABA + 2.5 g/l AC (EDMM). Individually separated somatic embryos were germinated on both NN and half strength of MS containing 0.5 μM BA + 0.025 μM NAA, respectively; normal plantlet conversion from embryos was low (35%). Whole fruiting plants were obtained. Aberrant embryo development was characterized by failure to form functional shoot meristems following the initial cotyledon expansion during germination. These observations indicate that the embryo conversion stage of the regeneration is difficult and remains a limiting factor requiring more empirical experimentation for improvement in grape tissue culture. Key words: Chancellor grape, Regeneration, Somatic embryogenesis D.O.I. 10.3329/ptcb.v20i2.6895 Plant Tissue Cult. & Biotech. 20(2): 157-170, 2010 (December)